Ruminal degradability of alfalfa in the Costa Rica’s Central Valley, Eastern zone - Boschini Figueroa, Carlos; Chacon-Hernandez, Pablo (Agronomía Mesoamericana, 2017)
The objective of this work was to evaluate in dairy cows, the potential of ruminal degradability of four alfalfa (Medicago sativa) varieties developed in Argentina. The research was carried out in the Alfredo Volio Mata Experimental Station, located in the province of Cartago, Costa Rica; the area has a mean temperature of 17.9°C; a height of 1542 masl, and 1465.9 mm of rain evenly distributed between the months of May and November. Sampling was performed during 2014’s rainy season with ground level harvest of alfalfa, with samples of the varieties of Mora, Patricia, Victoria and Super Monarca, with harvest age of 28, 35, 42, 49, 56 and 63 days; all samples were dried, minced and incubated by duplicate on two Jersey-Reyna ruminally fistulated cows, for 0, 3, 6, 12, 24 and 48 hours. The results were analyzed through the Marquardt algorithm with the SAS software. Statical differences were only found between soluble fraction and degradation rate (p<0.05) according to harvest ages, with values of soluble, potentially degradable and degradation rate of 35.34%-44.65%, 36.46%-39.96% and 0.0734/h-0.1176/h, respectively. Likewise, effective degradability percentages of 59.06%-67.09%, with passage rates of 6%/h, according to harvest ages were obtained. Given the obtained results, the analyzed varieties of M. sativa showed a digestible forage, which could be used for the feeding of highly production animals.